Is suffering a sufficient legitimation for UTx?. (9th February 2023) - Bozzaro, Claudia; Weismann, Melanie; Westermann, Anna Maria; Alkatout, Ibrahim
Abstract: Uterus transplantation is a relatively new intervention. A woman with absolute uterine factor infertility receives, by a surgical procedure, a transplanted uterus, most often by living donation. The uterus recipient may thus become pregnant and conceive her own child. As with any other medical treatment, UTx requires legitimation. The anticipated benefits must outweigh the risks of the medical intervention. The risks and benefits of UTx are by no means unequivocal and cannot be easily determined. The benefits depend on the final evaluation of the suffering to be alleviated by the intervention. In the following, we will analyze the suffering addressed by UTx and discuss its normative value. First, we point out that (a) suffering is generally considered an important normative criterion in medicine as well as in the context of UTx; (b) we then describe the risks and anticipated benefits of UTx for the three persons directly concerned: the child, the donor, and the recipient; (c) we further analyze the suffering addressed by UTx. The intervention addresses a form of existential suffering. We discuss the common notion that existential suffering should be evaluated from the subjective perspective of the sufferer; (d) afterwards, we argue that in a social practice like medicine, a one‐sided evaluation stemming from the sufferer alone is not sufficient; and (e) finally, arguments from a societal perspective lead us to the conclusion that the existential suffering addressed by UTx does not possess a sufficiently strong normative value to legitimize a high‐risk, expensive procedure.